ANALYZING THE ROLE OF EMPOWERMENT IN MEDIATING EFFECT OF KNOWLEDGE MANAGEMENT ON OCB - Rita Aryani; Widodo Widodo (JABE (Journal of Applied Business and Economic), 2020)
This study analyzes the effect of knowledge management on organizational citizenship behavior (OCB) mediating by empowerment. The research data was collected by a questionnaire through the survey methods toward 375 teachers. Data analysis uses path analysis supported by descriptive statistics. The results show that knowledge management had a significant effect on OCB mediating by empowerment. Thus, the teacher’s OCB can be improved through knowledge management and empowerment. This finding can be discussed as a reference among researchers and practitioners to develop better models of OCB in the future and various contexts of organizations.